Encouraging Students to Learn English Through Topic-based Approach in a Rural Public School in Guarne (2019)
ABSTRACT: This action research project was developed in order to analyze the effect of a theme-based unit applied in a rural school in Guarne and the way it engaged the students throughout the course to learn the target language. This project was carried out in a public school to a group of thirty students of the eighth grade of men and women. In the action part, a topic-based unit about life in a rural area was designed and implemented in the second term of the academic year. Interviews, surveys and a journal were performed to collect the data for the analysis. Such findings displayed three categories which allowed to obtain some conclusions about the promotion of positive attitudes in the students towards the learning of English.